IMPACT OF EDUCATIONAL CONCEPT ON INFORMATION AND DIDACTIC SUPPORT OF ACADEMIC DISCIPLINES HIGH SCHOOL - Кириченко, В.І.; Бойченко, С.В. (Proceedings of National Aviation University (archive), 2012)
The problems associated with the development of innovative educational concept of higher technical education and its impact on the level of perfection the information and didactic ensure the educational process in the basic disciplines, and hence on the efficiency and quality of education, the formation of systems thinking and the student's creative personality traits